Essential shorinjiryu karatedo - Hisataka, Masayuki Kukan
In Essential shorinjiryu karatedo, Masayuki Kukan Hisataka, ninth Dan Black Belt Karate master, introduces the highly innovative and effective shorinjiryu kenkokan karatedo system. though an integral system of Okinawa karate practiced for centuries, it is an evolving scientific martial art that incorporates elements from kungfu, Kudakajima Shishiryu bo jutsu, and Western and Oriental medicine. In this detailed work, Master Hisataka demonstrates the techniques, fighting combinations, and kata (present forms) that have made him a leading international master of both karate and judo. The text describes in detail basic karate strikes, kicks, and blocks, as well as the philosophy of yin-yang and the five elements and how that philosophy relates to fighting strategy and attitude. The history and development of karate from ancient times are covered in detail, with focus on the Okinawan masters who brought karate to Japan. This book's 430 photographs show karate fighting techniques in action, illustrating a variety of effective striking combinations, counters, and three classical karate kata. This is also the first book in English to show the use of Supersafe protective equipment in martial arts training.